An Analysis of Classroom Intercation in Speaking Classes at a Junior High School - Maharani , Indah Permata; Irfani, Bambang; syamsiah, Nur Syamsiah (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This study aims to explore classroom interaction in speaking learning at SMPN Sekuting Terpadu using the Flanders Interaction Analysis Category System (FIACS) to examine communication patterns and identify the most frequently used learning strategies by English teachers. Effective classroom interaction is very important in language learning because it can improve students' speaking ability, self-confidence, and communicative competence. This study uses a qualitative descriptive method with data collection techniques in the form of interviews, observations, and focus group discussions (FGD). Participants in this study were students and an English teacher from classes 8A and 8C. Data analysis was carried out through data condensation, data presentation, and drawing conclusions. The results showed that classroom interaction was dominated by teachers in both classes. In class 8A, teacher interaction reached 52% of the total interaction, mainly in the form of questions, giving instructions, and praise, while student responses were only 34%, and 12% of the time was filled with silence or confusion. A similar pattern was found in class 8C, with teacher interaction at 53%, student responses at 30%, and silence/confusion at 12%. The most frequently used learning strategies include questioning techniques, direct instruction, and structured activities such as group discussions and role-plays. Open-ended questions have been shown to be effective in encouraging student participation and stimulating discussion, creating a more interactive and engaging learning environment.